Relationship of pressure and word-initial and word-final grapheme position in print handwriting of Spanish words (2019)
The aim of this study was to explore the development of pressure during the writing of words, as a fundamental parameter of the written signal, specifically in the handwriting of block letters, in Spanish. Studies using other types of writing and in other languages have observed the phenomenon of PROGRESSIVE MOTION VARIABILITY: pressure for word final letters was higher than for initial letters, which was also true for pressure variability. Forty university students participated and copied a set of 72 words, 36 of which started with one of the graphemes of interest ( less than a>, less than e>, less than l>, less than r>; e.g., abdomen); the other 36 words ended with one of these graphemes (e.g., diploma). A graphic tablet and electronic ink pen served to record the data. The word final grapheme showed a higher average pressure and pressure variability than the word initial grapheme. We also found differences between graphemes. This means that in Spanish the characteristics of the trace of a letter depend on letter identity but also on its position in the word. This is an important fact to take into account in future studies analyzing this parameter. © 2019 Universidad de Los Andes. All rights reserved.